Octopuses in wild and domestic relationships. (September 2018) - Scheel, David
People commonly interact with terrestrial domestic animals, such as dogs and cats, horses, cattle and goats, and birds. Thereby individuals of different species form animal–human bonds. We are now forming relationships with ocean animals in increasingly common ways through growing human populations, advances in technology such as SCUBA, ocean mapping, underwater instrumentation and advances in aquatic animal husbandry. Octopuses and humans share quite distant evolutionary ties and yet share aspects of sensory ability and intelligence. Octopuses thereby pose interesting challenges and conundrums for understanding animal–human relationships. I consider several reasons to expect that the evolution of octopuses, and of animal cognition generally among active and visually sophisticated animals, will favour traits that support relationships between individuals. The evolutionary outcome of animals capable of forming inter-individual relationships may thus be expected in any evolving biota with organisms of this kind. This article explores the ability of ocean and terrestrial animals to relate to one another in ways that are reciprocal, if not equally balanced, and illustrates this with the examples of octopuses.